Gender and Safety Nets : Priorities for Building Back Better - Heinemann, Alessandra; Beegle, Kathleen (World Bank, Washington, DC, 2021)
Achieving gender equality and economic inclusion is critical for economic growth and prosperity. The pandemic threatens to reverse hard-won gains towards gender equality. Before the crisis, women were more likely than men to be engaged in vulnerable forms of work in low- and middle-income countries, were overrepresented in sectors with the largest economic disruptions, and carried the brunt of increased care work. During the crisis, their income opportunities have taken a big hit. In Ethiopia, for example, women respondents to a phone survey conducted during the early stages of the pandemic were found to be more likely than men respondents to have lost their jobs (15 percent versus 12 percent) (Ambel et al. 2020). In Latin America, women workers were 44 percent more likely than men workers to lose their jobs at the onset of the COVID-19 crisis. Woman-led microbusinesses, in the hospitality industry, and in countries more severely affected by the COVID-19 shock was disproportionately affected compared with corresponding businesses led by men (Torres et al. 2021). Women and older girls also bear a disproportionate share of the care responsibilities arising because of school closures among family members affected by COVID-19. Reports of gender-based violence have increased around the world.